2022
DOI: 10.3389/fpsyg.2022.1014434
|View full text |Cite
|
Sign up to set email alerts
|

Integrating artificial intelligence into a talent management model to increase the work engagement and performance of enterprises

Abstract: The purpose of the paper is to create a multidimensional talent management model with embedded aspects of artificial intelligence in the human resource processes to increase employees' engagement and performance of the enterprise. The research was implemented on a sample of 317 managers/owners in Slovenian enterprises. Multidimensional constructs of the model include several aspects of artificial intelligence implementation in the organization's activities related to human resource management in the field of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 67 publications
(130 reference statements)
0
7
0
Order By: Relevance
“…Each of these concerns also affects organizational culture. As more and more machines enter the workforce, replacing human beings, questions are emerging on the changing cultural dynamics within firms (Frangos, 2022 ; RoŽman et al, 2022 ; Chowdhury et al, 2023a ). In the technocratic stage of AI-HRM implementation and usage it is important to develop and nurture an organizational culture of innovation (Fountaine et al, 2019 ; Pumplun et al, 2019 ; Ransbotham et al, 2021 ), collaboration (Fountaine et al, 2019 ), and effective change management (Pumplun et al, 2019 ).…”
Section: How Hrm Can Bring Humans and Machines Closer Together In The...mentioning
confidence: 99%
“…Each of these concerns also affects organizational culture. As more and more machines enter the workforce, replacing human beings, questions are emerging on the changing cultural dynamics within firms (Frangos, 2022 ; RoŽman et al, 2022 ; Chowdhury et al, 2023a ). In the technocratic stage of AI-HRM implementation and usage it is important to develop and nurture an organizational culture of innovation (Fountaine et al, 2019 ; Pumplun et al, 2019 ; Ransbotham et al, 2021 ), collaboration (Fountaine et al, 2019 ), and effective change management (Pumplun et al, 2019 ).…”
Section: How Hrm Can Bring Humans and Machines Closer Together In The...mentioning
confidence: 99%
“…This has led to both opportunities and challenges for Human Resource Management (HRM) in areas such as job displacement, AI-human collaboration, decision-making processes, and learning, training, recruitment, and job performance evaluation [11]. As studies have shown, AI integration into companies significantly enhances performance and employee engagement, leveraging various key areas, including the selection and retention of talented employees, the provision of suitable training and development, the formation of effective teams, a supportive organizational culture, the fostering of leadership, and a reduction in the employee workload [12].…”
Section: Perspectives On Essential Skills For Ai Integration Into Bus...mentioning
confidence: 99%
“…[9] Discussed utilizing artificial intelligence to deliver feedback to employees, with an emphasis on its capacity to automate performance assessments and enhance job performance. AI-based human-machine interaction technology has a direct impact on enterprise performance and employee satisfaction, according to [8] Additionally, Incorporating AI into talent management models increases employee engagement and enterprise performance, according to [6]. [2] AI has the potential to increase employee engagement, performance, and retention in human resource management, according to [1], who emphasized the significance of utilizing AI technology to assess employee performance and make strategic decisions.…”
Section: The Framework Of the Study 2 Review Of Literaturementioning
confidence: 99%